Neoplecostomus canastra, a new catfish (Teleostei: Siluriformes) species from upper Rio Paraná basin - Roxo, Fábio F. [UNESP]; Silva, Gabriel S. C. [UNESP]; Zawadzki, Cláudio H.; Oliveira, Claudio [UNESP] (Magnolia Press, 2017)
In this study, we describe a new species of Neoplecostomus from córrego Tamborete, municipality of Capitólio, Minas Gerais state, upper rio Paraná basin. The new species is distinguished from its congeners by the presence of conspicuous dark spots all over the body. Moreover, the new species can be diagnosed by the absence of moderate keels along each lateral series of plates, presence of developed adipose fin, absence of enlarged, fleshy folds between dentaries, dorsal-fin spinelet larger than dorsal-fin spine, lacking enlarged odontodes along lateral margins of snout and along ridges before eyes, having reduced number of dentary teeth, having two irregular and conspicuous rows of large and transversally-flattened papillae, just posterior to dentary teeth, smaller mandibullary width/head length, smaller Interorbital width/mandibullary width, smaller number of lateral-line plates, higher and lower number of dentary teeth depending of the species compared, absence of a conspicuous sexual dimorphism, absence of a conspicuous horseshoe-shaped light blotch posterior to the supraoccipital, with a central dark area which rarely contacts the edge of the light area, smaller mandibulary width/head length, smaller Interorbital width/Mandibullary width and a greater Caudal peduncle length/Caudal peduncle depth. Furthermore, we used DNA barcoding techniques of 2% threshold criteria and GMYC model to distinguish the new species from its congeners. These molecular techniques were unable to distinguish the new species from N. langeanii and N. selenae from N. botucatu, that were differentiated using external morphology.
Keywords: Freshwater fish; Loricariidae; Neoplecostominae; Neotropical fish; Taxonomy